Job performance and mental health in workforce in north macedonia during COVD-19 pandemic - Dimitrinka Jordanova Pesevska; Ana Tomovska Misoska; Kate Trajkova (University American College Skopje, 2021)
The COVID-19 pandemic is a major public health disaster having significant influence on economic, mental health and well-being of entire world population including North Macedonia. The existing literature is suggesting changes in the work performance and job satisfaction influencing mental health of employed individuals. The need for changes in "new normal" ways of working and performing in COVID-19 made a significant impact on mental health and well-being of the employees. Aim of the study is to explore the connection between the changes in workplace practices and task performance before and during the COVID-19 pandemic among employees and their mental health. The study is a cross-sectional including 297 participants, employed adults from the general population in North Macedonia. The convenient sample is based on a snowball recruitment of the participants. The following self-reported measurement were used in the study: Depression, Anxiety and Stress Scale (DASS-21) short version for determining stress and anxiety, adopted version of Individual Work Performance Questionnaire(IWPQ) and instrument for measuring the task performance changes in workplace practices questions are aligned with the questions from a large study on work-related consequences of COVID-19 across Europe. Results showed that being females and younger is associated significantly with higher levels of both stress and anxiety (t (267)=2.82, p=.005). The results from the regression analyses showed that perception of task performance in the last three months; the increased difficulty of work due to the pandemic requirements, and change in meeting other people are significant predictors for stress in employees. The study also revealed that significant predictors for anxiety are increased difficulty of work which has positive relations with anxiety and increased workload, which has negative relation with anxiety.
Keywords: 330; COVID-19; mental health; workforce; practices; task performance